Transfersal Transformation: From Personal Analysis to Social Analysis According to Calvin and Ricoeur - Simon, John C. (Journal of Asian Orientation in Theology, 2019)
Two figures who live in different ages, Calvin and Ricoeur, have built their thinking by way of an experience of repentance or self-renewal. It is this experience what so-called as personal analysis. Calvin, with his experience of "sudden conversion (subita conversio)", was moved to undertake a better world transformation as the stage of God's glory. Ricoeur, with his concept of self-consciousness", emancipated the open subject aimed at social emancipation. Their experiences are individual in character, but it isnt closed, conversely opened and forwarded out to others through relationships with others in the context of living together. Its goal is a social analysis through the transformation of a good and just life. The shifting process from personal analysis to social analysis, I name it as a transfersal transformation, namely, a change in the private realm that is forwarded to the public sphere with a call to live a good and fair life together.In Asia, the shift from personal analysis to social analysis (transfersal transformation) is important for Asian theology to be contextual and design a good and just society.